Drug use treatment and harm reduction programs in Iran: A unique model of health in the most populated Persian Gulf country - Alam-Mehrjerdi, Z.; Abdollahi, M.; Higgs, Peter; Dolan, K. (Elsevier, 2015)
Because of the proximity of Persian Iran to Afghanistan, the main opium producer in the world, drug use especially opium use has a long history in Iran. Opium and its residues are the traditional drugs while heroin, heroin Kerack, norgesic, temgesic, and methamphetamine use and injection have emerged more recently. In recent decades, heroin smoking and injection have presented challenges to the Persian health policy makers to accept and develop the internationally-approved programs of drug use treatment and harm reduction. The current paper summarizes the overall picture of main drugs used and the history of establishing the nationwide movement of drug use treatment and harm reduction programs after the 1979 revolution until the end of 2014. The paper concludes that Persian Iran has a well-developed healthcare system in the provision of drug use treatment and harm reduction programs in the south-west of Asia especially the Persian Gulf region. These therapeutic and harm reduction-related programs are required to be strengthened by opium supply reduction and eradicating drug production in Afghanistan. The provision of prevention programs, drug education via mass-media, employment and inexpensive leisure activities are required in Iran. In addition, conducting household surveys of the prevalence of drug use and evaluating the clinical effectiveness and treatment outcomes of the provided drug treatment and harm reduction programs are required. National and regional collaborations are rigorously suggested to manage supply reduction along the borders and implement demand reduction inside the borders.